2021
DOI: 10.1016/j.jbc.2021.100334
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of amyloidogenic mutations in hypervariable regions of antibody light chains

Abstract: Systemic light chain (AL) amyloidosis is a fatal protein misfolding disease in which excessive secretion, misfolding, and subsequent aggregation of free antibody light chains eventually lead to deposition of amyloid plaques in various organs. Patient-specific mutations in the antibody V L domain are closely linked to the disease, but the molecular mechanisms by which certain mutations induce misfolding and amyloid aggregation of antibody domains are still poorly understood. Here, we comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 88 publications
(82 reference statements)
0
38
0
Order By: Relevance
“…Changes in primary structure introduced by somatic hypermutation into the germline sequence or by posttranslational modifications are also discussed as drivers of light chain aggregation [8,17]. The identification of critical amino acid positions and their concentration in specific secondary structure regions showed that the location and nature of the mutation, rather than the number, determines the amyloidogenicity of light chains [18][19][20][21][22]. Some mutations have been attributed to a decrease in thermodynamic stability [18,[23][24][25], increase in conformational dynamics [17,20,21] or effects on interdomain interactions [26,27].…”
Section: Properties Of Amyloidogenic Light Chainsmentioning
confidence: 99%
“…Changes in primary structure introduced by somatic hypermutation into the germline sequence or by posttranslational modifications are also discussed as drivers of light chain aggregation [8,17]. The identification of critical amino acid positions and their concentration in specific secondary structure regions showed that the location and nature of the mutation, rather than the number, determines the amyloidogenicity of light chains [18][19][20][21][22]. Some mutations have been attributed to a decrease in thermodynamic stability [18,[23][24][25], increase in conformational dynamics [17,20,21] or effects on interdomain interactions [26,27].…”
Section: Properties Of Amyloidogenic Light Chainsmentioning
confidence: 99%
“…The recombinant light chain FOR005 refers to the light chain of an ALλ amyloidosis case with cardiac involvement. Recombinant light chain FOR005 was expressed and purified as previously described [29]. Briefly, the DNA plasmid (pET28b) encoding for FOR005 light chain was transformed into Escherichia coli BL21 (DE3)‐star cells and the protein was expressed as insoluble inclusion bodies over night at 37°C using 1 mmol/L isopropyl β‐D‐1‐thiogalactopyranosid for induction.…”
Section: Methodsmentioning
confidence: 99%
“…Somatic mutations in the IgL genes, generated in the process of immunoglobulin synthesis, add complexity to the IgL structure. The burden of the somatic mutations and the specific site that a mutation occurs can influence the stability and amyloidogenicity of IgL [91][92][93][94][95]. A model from a recent study based on somatic mutations in IgL displays high sensitivity and specificity to predict the free light chain toxicity [96].…”
Section: Genomic Alterations Related To Amyloid Formationmentioning
confidence: 99%